2022
DOI: 10.22454/fammed.2022.331576
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment and Gender Bias in Family Medicine: Divergent Experiences of Men and Women

Abstract: Background and Objectives: Awareness of sexual harassment (SH), gender bias (GB), and gender discrimination (GD) has spread throughout popular culture and has been highlighted at universities across the United States. More nuanced data is needed to inform policies that address these issues. However, there are currently limited qualitative studies examining the nature of SH, GB, and GD in academic medicine, particularly family medicine. Methods: In 2018, we conducted a series of gender-specific focus groups wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…1 Respondents' experience of SH and GB is associated with lasting psychological effects that mainly spared the men in our department. 2 These findings are consistent with those reported in other disciplines.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…1 Respondents' experience of SH and GB is associated with lasting psychological effects that mainly spared the men in our department. 2 These findings are consistent with those reported in other disciplines.…”
Section: Introductionsupporting
confidence: 91%
“…We explored the lived experiences of our faculty and learners through focus groups. 1,2 We then presented our findings to faculty and triangulated data with faculty feedback and discussion of the data. Based on these results, we developed trainings to reinforce the department's stance against harassment and discrimination, to develop shared behavioral expectations and to educate all members of our department about policies and procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Sanders et al. (2022) found that age and positions of power moderated experiences of sexual harassment, gender bias and discrimination, such as patients' stereotypes regarding women's roles, comments on physical appearances and sexist jokes and remarks; participants noted that having grey hair or wearing a doctor's coat shielded them from these experiences. Pololi et al.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis revealed a need for a nuanced approach in addressing moral distress. Gender considerations, for instance, could inform interventions by recognizing women's experiences of moral distress were found to be particularly heightened by societal gender roles and expectations and gender‐based violence and discrimination (Boakye et al., 2021; Monrouxe et al., 2015; Nemati et al., 2021; Sanders et al., 2022; Shoorideh et al., 2015). Policies that protect women against bias and sexual harassment, alongside redress mechanisms, could be effective in reducing incidents of moral distress among women healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation